Atmospheric Pb and Ti accumulation rates from Sphagnum moss: dependence upon plant productivity - Kempter, Heike; Krachler, Michael; Shotyk, William (Environmental science & technology, 2010)
The accumulation rates of atmospheric Pb and Ti were obtained using the production rates of Sphagnum mosses collected in four ombrotrophic bogs from two regions of southern Germany: Upper Bavaria (Oberbayern, OB) and the Northern Black Forest (Nordschwarzwald, NBF). Surfaces of Sphagnum carpets were marked with plastic mesh and one year later the production of plant matter was harvested. Metal concentrations were determined in acid digests using sector field ICP-MS employing well established analytical procedures. Up to 12 samples (40 × 40 cm) were collected per site, and 6−10 sites were investigated per bog. Variations within a given sampling site were in the range 2.3−4× for Pb concentrations, 1.8−2.5× for Ti concentrations, 3−8.3× for Pb/Ti, 5.6−7.8× for Pb accumulation rates, and 2.3−6.4× for Ti accumulation rates. However, the median values of these parameters for the sites (6−10 per bog) were quite consistent. The mosses from the bogs in NBF exhibited significantly greater productivity (187−202 g m−2 a−1) compared to the OB peat bogs (71−91 g m−2 a−1), and these differences had a pronounced effect on the Pb and Ti accumulation rates. Highly productive mosses showed no indication of a “dilution effect” of Pb or Ti concentrations, suggesting that more productive plants were simply able to accumulate more particles from the air. The median rates of net Pb accumulation by the mosses are in excellent agreement with the fluxes obtained by direct atmospheric measurements at nearby monitoring stations in both regions (EMEP and MAPESI data).